ROLE OF ANTIOXIDANTS CYSTEINE AND TAURINE IN TRIS EGG YOLK BASED EXTENDER FOR CRYOPRESERVATION OF SURTI BUFFALO SEMEN - VARGHESE, ORIN; DHAMI, A J; HADIYA, K K; PATEL, J A; PARMAR, S C (The Indian Journal of Animal Reproduction, 2023)
The study was undertaken on 40 semen ejaculates collected from 5 Surti bulls (8 ejaculates per bull). Ejaculates with >70% initial motility were split into 5 equal fractions and were diluted with standard Tris citrate fructose egg yolk glycerol (TFYG) extender as control and TFYG having 2 additives Cysteine HCI (0.5 & 1.0 mg/ml) and Taurine (4.0 & 6.0 mg/ml) each at 2 levels to study their comparative efficacy for cryopreservation of buffalo spermatozoa. After 12-24 hrs of cryopreservation, each of the 5 split-samples were thawed in water bath at 37°C for 30 seconds and observed for post-thaw motility, viability, morphology, acrosomal integrity and plasma membrane integrity. The post-thaw longevity of sperm at 37°C incubation was also studied for 3 hrs. Highly significant (P<0.01) variations among five extender-additive formulations, viz., control TFYG extender, TFYG + cysteine @ 0.5 mg/ml, TFYG + cysteine @ 1 mg/ml, TFYG + taurine 4 mg/ml and TFYG + taurine 6 mg/ml were observed at pre-freeze stage in sperm motility (65.37±0.84, 68.37±0.81, 72.62±0.69, 73.25±0.81 and 71.12±1.02 %), viability (72.75±0.99, 70.62±0.81, 78.97±0.93, 79.37±0.88 and 76.32±1.14 %), total sperm abnormalities (6.35±0.27, 5.73±0.28, 5.45±0.25, 5.80±0.28 and 6.38±0.29 %), acrosomal integrity (89.70±0.39, 90.58±0.34, 90.90±0.35, 88.53±0.46 and 86.28± 0.45 %) and HOS reactive sperm (70.82±0.92, 74.17± 0.93, 78.12±0. 79, 78.08±0.95 and 75.03±1.08 % ); and so also in post-thaw sperm motility (38.37±0.95, 39.50±0.80, 46.50± 0.72, 50.00±0.62 and 34.25±0.71 %), viability (44.82±1.02, 46.37±0.99, 52.97±0.79, 55.02±0.80 and 41.07±0.99 %), total sperm abnormalities (9.10±0.22, 8.15±0.26, 7.10±0.26, 7.90±0.29 and 8.90±0.31 %), acrosomal integrity (82.43±0.32, 84.40±0.18, 85.73±0.18, 82.75±0.30 and 79.98±0.35 %) and HOS reactivity (42.52±1.04, 45.10±1.04, 51.62±0.82, 53.73±0.69 and 39.10±0.91 %). At all the stages of cryopreservation process, post-thaw stage and after incubation in particular, semen diluted with TFYG + taurine 4 mg/ml and TFYG + cysteine @ 1 mg/ml showed significantly better preservation of all sperm quality parameters than other extender additives. Thus TFYG + taurine 4 mg/ml or TFYG + cysteine @ 1 mg/ml can be recommended as better extender-additive for cryopreservation of buffalo semen.